Ocultar e preservar: a saga da civilidade em São Luís do Maranhão - CAMÊLO, Júlia Constança Pereira (Universidade Federal do Pará, 2014)
The thesis approachs the city of São Luis of Maranhão in the end nineteenth and twentieth centuries. Analyzes aspects of the imaginarium about the town located on an island and that see itself integrated into the mainland, the country and Europe. It discusses the prospect of American civilization from the thought of Rodó, Fecundo, Manoel Bonfim, Leopoldo Zea and the way the residents of São Luis sought recognition of the city as owner of civility. Analyzes how the people of São Luis – the “ludovicensis” - dealt with the marks of slavery like evidence of barbarism, and as the thought of the nineteenth century, should be eradicated. Approach the process that turned the popular manifestation “bumba meu boi” into a symbol of the culture of the city, before something barbaric, condemned the suburb of the island. It shows that preservation observed in the photo albums of the town was ???"fronts"??? , but safeguarded mansions of the nineteenth century and provided a new classification of São Luis as the fifth city in Brazil to receive the title of World Heritage Sites, a return, a new insert, a highlight among the cities. The analysis was performed from iconographic sources, maps, literature, and newspapers.